Efficacy of Single-Position Oblique Lateral Interbody Fusion Combined With Percutaneous Pedicle Screw Fixation in Treating Degenerative Lumbar Spondylolisthesis: A Cohort Study - Cheng, Peng; Zhang, Xiao-bo; Zhao, Qi-ming; Zhang, Hai-hong (Frontiers in Neurology, 2022)
Objective To investigate the surgical outcomes of single-position oblique lateral interbody fusion (OLIF) combined with percutaneous pedicle screw fixation (PPSF) in treating degenerative lumbar spondylolisthesis (DLS). Methods We retrospectively analyzed 85 patients with DLS who met the inclusion criteria from April 2018 to December 2020. According to the need to change their position during the operation, the patients were divided into a single-position OLIF group (27 patients) and a conventional OLIF group (58 patients). The operation time, intraoperative blood loss, hospitalization days, instrumentation accuracy and complication rates were compared between the two groups. The visual analog scale (VAS) and Oswestry Disability Index (ODI) were used to evaluate the clinical efficacy. The surgical segment's intervertebral space height (IDH) and lumbar lordosis (LL) angle were used to evaluate the imaging effect. Results The hospital stay, pedicle screws placement accuracy, and complication incidence were similar between the two groups (P > 0.05). The operation time and intraoperative blood loss in the single-position OLIF group were less than those in the conventional OLIF group (P < 0.05). The postoperative VAS, ODI, IDH and LL values were significantly improved (P < 0.05), but there was no significant difference between the two groups (P > 0.05). Conclusions Compared with conventional OLIF, single-position OLIF combined with PPSF is also safe and effective, and it has the advantages of a shorter operation time and less intraoperative blood loss.